Managing Gestational Diabetes Postpartum. Issue 4 (July 2018) - Killion, Molly M.
Abstract : Women who develop gestational diabetes during pregnancy are at increased risk for the disease in future pregnancies and for type 2 diabetes later in life. Our maternity nursing expert, Molly Killion, discusses important information that should be offered to women with gestational diabetes during the postpartum period so they can plan lifestyle modifications to promote optimal health.